2017
DOI: 10.1039/c7fo00076f
|View full text |Cite
|
Sign up to set email alerts
|

Potential antiproliferative activity of polyphenol metabolites against human breast cancer cells and their urine excretion pattern in healthy subjects following acute intake of a polyphenol-rich juice of grumixama (Eugenia brasiliensis Lam.)

Abstract: The bioavailability and metabolism of anthocyanins and ellagitannins following acute intake of grumixama fruit, native Brazilian cherry, by humans, and its in vitro antiproliferative activity against breast cancer cells (MDA-MB-231) were investigated. A single dose of grumixama juice was administered to healthy women (n = 10) and polyphenol metabolites were analyzed in urine and plasma samples collected over 24 h. The majority of the metabolites circulating and excreted in urine were phenolic acids and urolith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…These processes are known to influence psychological and cognitive resilience in, for example, animal models of social defeat and sleep deprivation. The collective evidence from our group and from other investigators [83, 122129] implicates gut-derived biologically available phenolic metabolites as primary facilitators of the observed health benefits associated with polyphenol rich diets.…”
Section: Polyphenols: Potential Therapeutic Applications In Neurologimentioning
confidence: 62%
“…These processes are known to influence psychological and cognitive resilience in, for example, animal models of social defeat and sleep deprivation. The collective evidence from our group and from other investigators [83, 122129] implicates gut-derived biologically available phenolic metabolites as primary facilitators of the observed health benefits associated with polyphenol rich diets.…”
Section: Polyphenols: Potential Therapeutic Applications In Neurologimentioning
confidence: 62%
“…However, some subjects excrete high amounts of polyphenol metabolites in the urine, whereas others excrete low amounts of metabolite. These findings indicate the high interindividual variability regarding polyphenol metabolism (45). Another recent study (43) showed that pomegranate ellagitannins differently improved CVD biomarkers depending on the individual's urolithin metabotypes (UM).…”
Section: Effects Of Gut Microbiota On Polyphenolsmentioning
confidence: 91%
“…Pedunculagin, strictinin, castalagin, vescalagin [12] 16 [12] Chestnuts (Castanea sativa) Castalagin [7] 149 [13] Pecans (Carya illinoinensis) Pedunculagin [7] 316 [13] Walnuts (Juglans regia) Pedunculagin, casuarictin [14] 864 [13] local importance have been identified such as jabuticaba [4], guava, [5] and grumixama cherries [12]. It is interesting to note that according to a Brazilian research team, Jabuticaba berries from a particular variety cultivated in south Brazil have the highest registered ET content in fruits.…”
Section: Food Occurrence Of Ellagitanninsmentioning
confidence: 99%
“…This inhibition was attributed to a significant G2/M cell cycle arrest (apoptosis) occurred in MDA-MB-231 cells, and was demonstrated by the increase in sub-G0/ G1 populations. Additionally, the authors linked this inhibition to a possible synergy among anthocyanins and urolithins [12]. Then, the modulation of the positiveestrogen receptor in breast cancer cells (MCF7) is probably one of the potential actions of urolithin conjugates.…”
Section: Chemoprevention Of Cancersmentioning
confidence: 99%